2018
DOI: 10.1128/aac.00922-18
|View full text |Cite
|
Sign up to set email alerts
|

New Locus of Drug Resistance in the Human Cytomegalovirus UL56 Gene Revealed by In Vitro Exposure to Letermovir and Ganciclovir

Abstract: Letermovir is a human cytomegalovirus (CMV) terminase inhibitor recently approved as prophylaxis in stem cell transplant recipients. In further studies of emerging drug resistance, a baseline laboratory CMV strain was serially propagated in cell culture under a combination of letermovir and ganciclovir. In eight experiments, UL56 terminase gene mutations were detected beginning at 10 passages and included novel amino acid substitutions V236A, L328V, and A365S in a region previously associated with letermovir r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…The viral DNA rebound began before high‐dose steroid therapy was given at week 94. At week 100, viral genotypic analysis revealed a CMV UL56 mutation C325Y, which is known to confer absolute resistance to letermovir (50% inhibitory concentration increased by >8000‐fold over wild‐type) . The previously detected UL97 mutation M460V was again detected, but the UL54 mutation L516P was no longer detected.…”
Section: Case Reportmentioning
confidence: 70%
See 3 more Smart Citations
“…The viral DNA rebound began before high‐dose steroid therapy was given at week 94. At week 100, viral genotypic analysis revealed a CMV UL56 mutation C325Y, which is known to confer absolute resistance to letermovir (50% inhibitory concentration increased by >8000‐fold over wild‐type) . The previously detected UL97 mutation M460V was again detected, but the UL54 mutation L516P was no longer detected.…”
Section: Case Reportmentioning
confidence: 70%
“…In the literature, the median duration of ganciclovir therapy prior to detection of resistance is about 22 weeks, although 3 of 17 lung recipients were reported to develop ganciclovir resistance much sooner . Extensive in vitro studies have reported the rapid evolution of letermovir resistance after drug exposure, much sooner than in parallel experiments with ganciclovir and foscarnet . Unlike ganciclovir and foscarnet, letermovir is affected by a single step mutation at UL56 codon 325 (C325) that confers absolute resistance with minimal to low impact on viral growth fitness .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping confirmed treatment-emergent UL56 mutations in two patients, while a third patient had clinical evidence of resistance. Serial viral passage under letermovir selective pressure has been associated with a relatively rapid selection of UL56 mutations, particularly within codons 231 to 369 (16,17). The possibility exists that the observed cases of letermovir resistance resulted from a selection of resistant subpopulations of CMV rather than as a consequence of a low barrier to resistance.…”
mentioning
confidence: 99%